2018
DOI: 10.1038/s41375-018-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MALAT1/PARP1/LIG3 complex induces DNA damage and apoptosis in multiple myeloma

Abstract: Metastasis-associated lung adenocarcinoma transcript 1(MALAT1) is a highly conserved long non-coding RNA (lncRNA). Overexpression of MALAT1 has been demonstrated to related to poor prognosis of multiple myeloma(MM) patients. Here, we demonstrated that MALAT1 plays important roles in MM DNA repair and cell death. We found bone marrow plasma cells from patients with monoclonal gammopathy of undetermined significance (MGUS) and MM express elevated MALAT1 and involve in alternative-non-homozygous end joining (A-NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 41 publications
(46 reference statements)
4
115
0
Order By: Relevance
“…As a corollary of our work, we provided evidence of MALAT1 druggability using LNA gapmeRs in vitro and in vivo in NOD-SCID mice bearing MM xenografts [152]. Hu et al reported that MALAT1 acts as a scaffold in the formation of PARP1/LIG3 complexes that recognize DSBs on DNA and activate the alternative non-homologous end joining (A-NHEJ) DNA repair in MM cells [151]. Moreover, MALAT1 inhibition by ASOs was proven to synergize both with PARP and proteasome inhibitors, and a nanoparticle-based approach significantly increased the in vivo delivery of MALAT1 inhibitors [151].…”
Section: Lncrnasmentioning
confidence: 55%
See 2 more Smart Citations
“…As a corollary of our work, we provided evidence of MALAT1 druggability using LNA gapmeRs in vitro and in vivo in NOD-SCID mice bearing MM xenografts [152]. Hu et al reported that MALAT1 acts as a scaffold in the formation of PARP1/LIG3 complexes that recognize DSBs on DNA and activate the alternative non-homologous end joining (A-NHEJ) DNA repair in MM cells [151]. Moreover, MALAT1 inhibition by ASOs was proven to synergize both with PARP and proteasome inhibitors, and a nanoparticle-based approach significantly increased the in vivo delivery of MALAT1 inhibitors [151].…”
Section: Lncrnasmentioning
confidence: 55%
“…To date, only a few lncRNAs have been functionally investigated in MM-including MALAT1 [151][152][153], NEAT1 [154,155], CCAT1 [156] and H19 [157,158]. Importantly, different reports converge in defining the oncogenic role of MALAT1 in MM, which was found upregulated during the progression from intra-medullary to extra-medullary disease, with the higher levels associated with shorter OS and PFS [153].…”
Section: Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA damage and repair are double-edged swords in cancer. DNA damage, coupled with error-prone repair, could drive cancer progression by promoting genomic or genetic instability (Doksani and De Lange, 2016;Hu et al, 2018). Based on our data analysis result, we infer that the DNA repair in response to DNA damage provides a possibility to prevent CRC cells from progressing.…”
Section: Genetic and Epigenetic Progression Mechanisms From Mid-stagementioning
confidence: 71%
“…The first pathway starts with receptor GRID2, which also appears in mid-stage CRC cells, and transmits the signal to TF WDR4 to upregulate target gene LIG3. LIG3 has been investigated in studies concerning DNA repair (Murray et al, 2011;Hu et al, 2018). DNA damage and repair are double-edged swords in cancer.…”
Section: Genetic and Epigenetic Progression Mechanisms From Mid-stagementioning
confidence: 99%